Levantamento e caracterização da avifauna dispersora de Rapanea ferruginea (Ruiz & Pav.) Mez. (Myrsinacea) - Marques, Kayo Victor Santos [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
This work evaluates the possibility of flora and fauna interactions being used in the ecological restoration of degraded environments, focusing on the use of Pera glabrata (Tamanqueira) to attract frugivorous birds with high efficiency in seed dispersal. In this literature review, were compiled articles about frugivory and seed dispersal of P. glabrata by birds, the results of these articles were compared with similar works on other native plant species to identify the bird species with the greatest potential for seed dispersal, by the birds foraging habits, mainly the habit of swallowing seeds whole. The morphological and phytosociological characteristics of Tamanqueira were also analyzed, such as its life habit; crown height and shape; flowering and fruiting periods; morphology and number of fruits; and its distribution throughout the national territory. The results obtained verified the ability of Tamanqueira to attract birds of high efficiency in the dispersion of seeds, from it and other plant species, among the avifauna sampled in the analyzed articles, Thraupis sayaca, Turdus leucomelas, Dacnis cayana, Vireo olivaceus, Turdus amaurochalinus and Empidonomus varius was highlighted as dispersers of a great diversity of native zoochoric plants. The pioneering habits of Tamanqueira allow a quick occupation with the shading of the slowly developing seedlings, while its abundant fruiting and its evergreen canopy provide food and shelter for the local birds, which allows the dispersion of seeds from the region in the ecological restoration site. The P. glabrata has the largest distribution range of the genus Pera and was recorded in several states from north to south of Brazil, in different physiognomies of Brazilian biomes. The plant specie analyzed in this work showed excellent potential for use in ecological restoration projects, helping in the natural insertion of seeds from regional vegetation by zoochory, can be used in ecological succession projects, together with pioneer and "climax" regional species, corroborating the hypothesis elaborated in this work.

A floração, frutificação e dispersão de sementes são etapas fundamentais no ciclo de reprodução de diversas espécies vegetais. A dispersão é um mecanismo que esses indivíduos possuem para se estabelecer em áreas diferentes e, consequentemente, distantes do seu local de origem. O processo em que as sementes e frutos são dispersos da planta mãe é definido como síndrome de dispersão. A ornitocoria é uma ferramenta de dispersão pela avifauna, um processo simbiótico onde as plantas tem suas sementes levadas para longe diminuindo a competição entre plântula e planta mãe. Pela sua abundância e frequência com que se alimentam de frutos, as aves figuram entre os mais importantes dispersores de sementes. Dessa maneira, o objetivo desse trabalho foi em reunir através da revisão bibliográfica as espécies dispersoras de Rapanea ferrugínea (Ruiz & Pav.) Mez. (Myrsinacea) bem como discutir a importância de tais espécies para essa dispersão e da árvore de estudo para a comunidade de aves. Encontrou-se nos artigos selecionados um total de 45 espécies, representantes de 4 ordens e 17 famílias. De acordo com o levantamento, Turdus amaurochalinus, Dryocopus lineatus e Turdus leucomelas foram as espécies que mais se alimentaram dos frutos, com um maior número de visitas e potencial dispersor. Apenas Turdus rufiventris foi reincidente nos trabalhos. Quanto a ocorrência por famílias, pode-se observar que os Tyrannidae foram a família com maior número de visitas, com 231 registros, seguidos dos Turdidae e Thraupidae. Além de um alto consumo por uma espécie especialista (Turdus amaurochalinus), é possível observar também a presença de espécies especialistas menos frequentes, como é o caso de Tityra cayana e Piprites pileata, reforçando a importância dessa árvore para a biodiversidade da comunidade de aves. Como uma espécie arbórea secundária, Rapanea Ferruginea também possui relevância em potenciais projetos de reflorestamento, visto que atraí toda uma comunidade associada de dispersores em seu período de frutificação.
Survey and characterization of the dispersing avifauna of Rapanea ferruginea (Ruiz & Pav.) Mez. (Myrsinacea)
Keywords: Frugivory; Zoochory; Birdlife; Animais; Ornitocoria; Aves; Rapanea ferruginea